2014
DOI: 10.1002/uog.13216
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation of new ultrasound‐based mathematical models for preoperative prediction of high‐risk endometrial cancer

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 20 publications
5
42
0
Order By: Relevance
“…We also validated on our dataset two two-step strategies for the prediction of high-risk cancer published previously 10 . Based on the two-step strategies, patients with a Grade-3 endometrioid or mucinous cancer or with other non-endometrioid malignancy on preoperative biopsy are classified as having a high-risk tumor (first step), while the remaining patients (Grade 1 and Grade 2) are classified using a prediction model (second step).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also validated on our dataset two two-step strategies for the prediction of high-risk cancer published previously 10 . Based on the two-step strategies, patients with a Grade-3 endometrioid or mucinous cancer or with other non-endometrioid malignancy on preoperative biopsy are classified as having a high-risk tumor (first step), while the remaining patients (Grade 1 and Grade 2) are classified using a prediction model (second step).…”
Section: Methodsmentioning
confidence: 99%
“…The 'subjective prediction model' includes biopsy grade (Grade 1 vs Grade 2) and subjective assessment of deep MI or CSI (present or absent) as variables. The 'objective prediction model' includes biopsy grade (Grade 1 vs Grade 2) and minimal tumor-free margin as variables 10 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a stratification of patients for surgery were based solely on the preoperative biopsy, then 64 % of high-risk patients would be erroneously underestimated according a multicentre study of Holsbeke et al [30].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Alcazar et al compared the diagnostic performance of six different approaches (impression of examiner, Karlsson's criteria, endometrial thickness, tumor/uterine 3D volume ratio, TDS and von Holsbeke's subjective model) for assessing myometrial infiltration using transvaginal/ transrectal US in endometrial carcinoma [22,23]. The study showed that the subjective impression seems to be the best approach for assessing myometrial infiltration in grade 1 or 2 endometrioid carcinoma and the use of mathematical models and other objective 2D and 3D measurement techniques do not improve diagnostic performance.…”
Section: Myometrial Infiltrationmentioning
confidence: 99%